Palaeoenvironmental study of two new foraminifera sites from Late Pleistocene transgressive deposits, northeast Buenos Aires Province, Argentina - Petriella, Julieta (2025)
This study examines the palaeoenvironmental evolution of two Late Pleistocene sites in northeastern Buenos Aires Province, Argentina, based on benthic foraminiferal records. The sites, Parque Pereyra Iraola (PPI) and Sanvol quarry (CSV), reveal significant insights into past coastal dynamics. At PPI, ten species from four genera were identified, whereas CSV yielded six species across four genera. Key species included Ammonia tepida, A. parkinsoniana, Elphidium galvestonense, Cribroelphidium poeyanum, C. gunteri, and Buccella peruviana, the latter found predominantly at CSV. The sedimentary analysis revealed a shallow marine environment at CSV with more restricted conditions at PPI, pointing to changes in hydrodynamics conditions. The deposits, found at elevations of 9-11 metres and intercalated with loess, are correlated with the MIS 5e transgressive event, establishing a strong temporal connection between the sites. The state of preservation also suggests high-energy depositional environments, likely influenced by storm events. This research emphasizes the utility of foraminiferal assemblages as environmental proxies, contributing to the understanding of coastal dynamics and sea-level fluctuations during the Late Pleistocene. By integrating micropalaeontological and sedimentological data, this study provides a framework for interpreting the responses of coastal systems to past climatic and sea-level changes, while also contributing to the broader context of Quaternary research.